Relationship trajectories of pregnant women with their parents and postpartum depression: A hospital-based prospective cohort study in Japan - Terada, Shuhei; Doi, Satomi; Tani, Yukako; Maeda, Yuto; Isumi, Aya; Sugawara, Junichi; Maeda, Kazuhisa; Satoh, Shoji; Mitsuda, Nobuaki; Fujiwara, Takeo (Frontiers in Psychiatry, 2022)
Backgrounds A history of childhood abuse and subsequent poor relationship with parents in adulthood among pregnant women is a known risk factor for postpartum depression (PPD). Although parent-daughter relationship can change during pregnancy, little is known whether the trajectories have an impact on PPD. The aim of this study is to examine whether trajectories of parent-daughter relationship during pregnancy are associated with PPD in Japanese mothers. Methods In a hospital-based prospective cohort study conducted in Japan, 4,772 women were followed from their first visit to their 1-month postpartum check-up (follow-up rate: 77.4%). Parent-daughter relationship was assessed whether participants were satisfied with their parents at first visit and after delivery. We defined four parent-daughter relationship trajectory categories: consistently satisfied, improving, deteriorating, and consistently unsatisfied. PPD was assessed by the Edinburgh Postnatal Depression Scale. Logistic regression model was applied to adjust covariates. Results There were 129 (2.7%), 122 (2.6%), and 181 (3.8%) cases of improving, deteriorating, and consistently unsatisfied relationship, respectively. Compared to the group that was consistently satisfied, pregnant women of the deteriorating and consistently unsatisfied group showed 2.81 (95% CI: 1.73–4.55) and 2.39 (95% CI: 1.58–3.62) times, respectively, more likely to show PPD after adjustment for confounders. Conclusion Women who felt that their relationship with parents “deteriorated” or was “consistently unsatisfactory” during pregnancy showed significant risk of PPD. Paying attention to the pregnant women's feelings about the relationship with their parents and promoting positive change may help predict and prevent PPD.